Novel Aspects of Lipoprotein Metabolism with Focus on Systemic Inflammation - Dullaart, Robin P.F. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
With cardiometabolic diseases still topping the list of mortality causes and in facing the obesity and diabetes epidemic, there remains a great need to better understand the pathophysiological derangements underlying these conditions. During the past years, it has become increasingly appreciated that low grade systemic inflammation is a common hallmark of cardiometabolic disorders—not only concerning diabetes and atherosclerotic cardiovascular disease but also involving non-alcoholic fatty liver disease. Recently developed high-throughput laboratory techniques for lipidomics and metabolomics have enabled researchers to discern novel crosstalk pathways between lipid phenotypes and enhanced chronic inflammation. With this Special Issue of the Journal of Clinical Medicine, entitled “Novel Aspects of Lipoprotein Metabolism with a Focus on Systemic Inflammation”, researchers were invited to submit original papers and reviews on various topics, in particular, at the interface of lipid metabolism and inflammation.